CAD Analysis of Freight Hopper Wagon using Ansys - Kethavath Lakpathi, G. Bikku Rahulji Dala (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Estimation of the Railway vehicle dynamic behavior utilizing the prototype is exceptionally expensive, lengthy and dull task. Thus, the greater part of the researchers and railway organizations are utilizing a railway show which is a virtual prototype and running it in virtual environment for foreseeing dynamic behavior of railway vehicle demonstrate. There is some well-known programming accessible for demonstrating like auto cad and pro -e, foreseeing dynamic behavior of vehicle model, for example, ANSYS, UNIVERSAL MECHANISM and so forth. At introduce steel material is utilized for container wagon, these will be replaced by aluminum compound in the closest future. In show work, I have designed and assembly of a proto sort model of fright hopper wagon utilizing CAD application. In PRO-E programming I have performed straight mode shape displaying and outline by hopper wagon on track. As the aluminum composite has more noteworthy quality and less self-weight, less fuel will be utilized as a part of transportation and vertical force is diminished, consequently less wear.